Analysis of Community Dependence on Non-Timber Forest Products in Community Forest Areas of Puncak Harapan Village Enrekang Regency - Fitra Ade Candra; Daud Irundu; Faradilah Farid Karim (Jurnal Hutan dan Masyarakat, 2025)
In the forest area in Puncak Harapan Village, we can find very active community interaction activities in the use of forest products in and out of the forest area. Forest utilization is still carried out in a simple way, so far the community is still carrying out NTFP management activities which only include raw or semi-finished raw materials. The income earned by the community from within the forest area will determine the extent of the community's dependence on forest products to fulfill their daily needs. This research aims to analyze how much dependence the community has on NTFPs in Puncak Harapan Village, Maiwa District, Enrekang Regency. The sample used in this research was 38 people using simple random sampling. The results of the research found six types of NTFPs that are used by the people of Puncak Harapan Village, namely sugar palm (Arenga pinnata), durian (Durio zibethinus), cloves (Syzygium aromaticum), candlenuts (Aleurites moluccana), bamboo (Bambusa Sp) and ginger (Zingiber officinale) which used directly or indirectly. Furthermore, the average annual income of people from within the forest area is IDR. 45,115,684/year/LLG or around 80% of the total annual income of the community, while the average value of HOK from within the forest area is 76.1 HOK/year/LLG or around 68% of the total average HOK so that the value obtained a percentage of 74% for the overall level of community dependence on NTFPs.